Ekspansi Teknologi : Degradasi Kapabilitas Mahasiswa dalam Berinteraksi Sosial - Desembrianti, Virna Muhdelifa; Agustina, Sheila; Triyono,; Hanna, Vinda Olivia (FisiPublik: Jurnal Ilmu Sosial dan Politik, 2023)
Nowadays, electronic devices have become a very important part of everyone's life. Gadgets in particular, not only make it easier for someone to gain access to information quickly, but gadgets are also used as communication tools, entertainment, and learning tools which make significant changes to the way people interact with the environment around them. Uncontrolled use of gadgets makes them waste a lot of time in front of the screen, this tends to have an impact on emotional intelligence. Sherry Turkle believes, "as technology ramps up, our emotional lives ramp down". Human emotional abilities or intelligence do not go hand in hand with technological advances. In his book, Turkle describes Henry David Thoreau's Three Chairs concept. David said, "in his cabin there were three chairs -one for solitude, two for friendship, three for society". This research uses a qualitative research method with a phenomenological approach. The qualitative research method is a research method that positions the researcher as the main instrument in the process of obtaining data. This research was conducted at Jember University, precisely on Jalan Kalimantan, Tegalboto No. 37, East Krajan, District. Sumbersari, Jember Regency. Jember University was chosen because it is relevant to the research topic that will be taken up by researchers. Based on the results of interviews and observations, the author found that students tend to choose to operate their smartphones when they are next to unfamiliar colleagues in class. When contacting a friend if they have an appointment to go out, they prefer to communicate via cellphone. However, if students prefer to spend time in front of gadget screens, they may miss this opportunity to interact